Genome‐wide association study identifies genomic loci associated with flight reaction in cattle. (11th December 2019) - Chen, Qiuming; Zhang, Fengwei; Qu, Kaixing; Hanif, Quratulain; Shen, Jiafei; Jia, Peng; Ning, Qingqing; Zhan, Jingxi; Zhang, Jicai; Chen, Ningbo; Chen, Hong; Huang, Bizhi; et al.
Abstract: Lower flight reaction is closely related to higher production in cattle, but the genetic basis of lower flight reaction is not clearly understood. Here, we sampled a total of 45 Brahman cattles and 166 Yunling cattles with flight distance (FD), and 73 Brahman cattles and 288 Yunling cattles with crush score (CS) and flight speed (FS), whereas there were 45 Brahman cattles and 161 Yunling cattles with all three traits. The FD, CS and FS in Brahman cattle were significantly lower than those in Yunling cattle. The flight reaction traits had negative correlation with conformational traits (e.g., body weight, withers height and body length). Based on SNPs derived from a subset of 162 whole genomes (25 Brahman genomes and 100 Yunling genomes with FD, 30 Brahman and 131 Yunling genomes with CS and FS), genome‐wide association study with mixed linear model was performed to test potential associations between flight reaction traits and genomic variants. We identified five, two and two genomic loci suggestively associated with FD, CS and FS, respectively. Five out of five candidate genes for FD ( LOC789753, LRP6, CTIF, SLC9A9 and ZEB1 ) were reported to be related to Alzheimer's disease representing cognitive impairment in human, which was consistent with the finding that cognitive‐behavioural intervention decreased the FD of cows to human. In CS, a very strong association locus was assigned to CDH8, a cadherin involved in synaptic adhesion, axon outgrowth and guidance, whose deletion was associated with autism spectrum disorder. In FS, a very strong association locus was assigned to GABRG2, a gamma‐aminobutyric acid (a major inhibitory neurotransmitter in brain) receptor, whose polymorphisms were associated with suicidal behaviour in schizophrenia patients. Our findings will provide targets for molecular‐marker selection and genetic manipulation of cattle improvement to meeting the growing demand for lower flight reaction to human.